The ethics of wild animal suffering - Ole Martin Moen (Etikk i Praksis: Nordic Journal of Applied Ethics, 2016)
Animal ethics has received a lot of attention over the last four decades. Its focus, however, has almost exclusively been on the welfare of captive animals, ignoring the vast majority of animals: those living in the wild. I suggest that this one-sided focus is unwarranted. On the empirical side, I argue that wild animals overwhelmingly outnumber captive animals, and that billions of wild animals are likely to have lives that are even more painful and distressing than those of their captive counterparts. On the normative side, I argue that as long as we have duties of assistance towards humans suffering from natural causes, and we reject anthropocentrism, we also have duties of assistance towards animals suffering in the wild. Article first published online: 22 MARCH 2016